IMPROVING VOCABULARY WHILE WATCHING KOREAN DRAMAS: A CASE OF INDONESIAN EFL UNIVERSITY STUDENTS - Aji Budi Rinekso; Okta Lesagia; Dian Setiawati (ELTR Journal, 2021)
Myriad studies have been discussing the role of subtitle for improving students’ vocabulary mastery. Yet, the use of English subtitle in Korean dramas is scarcely explored. Within a qualitative approach, this study aims at investigating how Indonesian EFL university students employ Korean dramas with English subtitle for improving their vocabulary. Twenty-three EFL university students were involved to participate in this study. Interview and questionnaire were applied as data collection methods. The results of the study revealed that the students enjoyed learning vocabulary through English subtitle while watching Korean dramas. They were motivated to learn vocabulary because of interesting storyline, editing effect and scene/setting served by Korean dramas. Pedagogically, this study implies that learning vocabulary can be done in regards with the students’ interests, including watching Korean dramas. Further research focusing on the employment of English subtitle for improving reading skill is interestingly to be carried out.